Carbon and oxygen isotope fractionation in the water-calcite-aragonite system. (15th August 2018) - Fohlmeister, Jens; Arps, Jennifer; Spötl, Christoph; Schröder-Ritzrau, Andrea; Plessen, Birgit; Günter, Christina; Frank, Norbert; Trüssel, Martin
Abstract: The precise determination of the stable C and O isotope fractionation between water and calcite (CC) and water and aragonite (AR) is of special interest for climate reconstructions, e.g. paleotemperatures. Previous studies reported results from both laboratory and field experiments, but their results are only partly consistent. Here we present C and O isotope data of a stalagmite from the Swiss Alps, which shows CC-AR transitions along individual growth layers. Using detailed analyses both laterally and perpendicular to such layers we examined the difference in the C and O isotope fractionation factor of the HCO3 − – CC and the HCO3 − – AR system. For O this difference is similar to the water-CC and water-AR offset provided in experimental studies. The O isotope fractionation difference in the water-CC and water-AR system is comparable to those determined in laboratory studies but shows a statistically significant correlation with the CaCO3 precipitation rate. For C we found a fractionation difference, which is independent of CaCO3 precipitation rate and with slightly smaller values for the fractionation offset between HCO3 − – CC and HCO3 − – AR compared to literature values. However, we also found an unexpected decrease in δ 13 C along growth layers, which contradicts the widely used concept of Rayleigh fractionation during CO2 degassing and CaCO3 precipitation. The results of this study can be used e.g., to correct stable isotope time series of stalagmites showing CC-AR transitions along their growth axes.